Assessing the prevalence of antimicrobial resistance among pediatric patients at Kamuzu Central Hospital, Malawi - Chitedze, Agness C; Mzikamanda, Rizine R; Maida, Tarsizio; McAtee, Casey L; Mapahla, Lovemore; Feasey, Nicholas; Nyasulu, Peter S (The Journal of Infection in Developing Countries, 2025)
Introduction: Severe bacterial infections cause significant disease burden in developing countries, including Malawi. The situation is compounded by the scarcity of resources, inconsistent availability of antibiotics, and increasing antimicrobial resistance (AMR). Methodology: This was a descriptive retrospective study where we analyzed blood culture results of pediatric patients admitted to Kamuzu Central Hospital (KCH), Lilongwe, Malawi. The data from January 2018 to January 2022 were compared with clinical metadata, and analyzed using the statistical software packages STATA version 16.1 and R version 4.2. Results: The data of 272 isolates from blood culture were obtained; 47.8% (130/272) of participants presented with organisms resistant to first-line antibiotics; 13.4% (22/164) were resistant to second-line antibiotics which included resistance to piperacillin/tazobactam and meropenem. Gram-negative isolates constituted 54.3% (89/164) of the isolates, of which 32% (29/89) were Acinetobacter spp; while 45.7% (75/164) of the isolates were Gram-positive of which 42.7% (32/75) was Staphylococcus aureus. There were 12 Escherichia coli isolates, of which 50% (6/12) were highly resistant to piperacillin/tazobactam. The Fisher’s exact test indicated that the antibiotic prescribed after a blood culture test result was significantly associated with the isolate observed (p = 0.016). Conclusions: This study highlights high rates of AMR to commonly used antibiotics in the pediatric ward at KCH, and calls for the need to revise treatment guidelines in the wake of empiric antibiotic choices for pediatric patients, including intensification of maximal use of blood culture tests as part of management of febrile illnesses and reinforcement of antimicrobial stewardship in pediatric patient care.